TH3.3: Fostering an enabling environment for equality and empowerment in agri-food systems - Lecoutere, Els; Achandi, Esther L.; Ampaire, Edidah L.; Fischer, Gundula; Gumucio, Tatiana; Najjar, Dina; Singaraju, Niyati (CGIAR GENDER Impact Platform, 2022)
Lasting transformative change in agri-food systems and wider societal benefits require fostering an enabling environment for empowerment and equality by gender and intersecting social differentiation, while concurrently reducing existing inequalities in access to and control over productive resources, services and technology, resilience and leadership. Fostering an enabling environment hinges on addressing key structural constraints to equally accessing resources, exercising agency and achieving desirable outcomes across multiple scales in a holistic manner. This paper discusses the emerging thinking about key structural barriers at the scales of the state, markets, communities, households and individuals that are rooted in policy, discriminatory (formal and informal) social and economic institutions (including social norms) and dampened aspirations; and their relevance for transformative change in agri-food systems. It shows the trend and current status of key structural constraints, and what has proven effective to relax such constraints. The paper lists key evidence-based recommendations to promote an enabling environment for empowerment and equality in agri-food systems.